2004
DOI: 10.1080/10255840410001710885
|View full text |Cite
|
Sign up to set email alerts
|

Congruency Effects on Load Bearing in Diarthrodial Joints

Abstract: Modelling load bearing in diarthrodial joints is challenging, due to the complexity of the materials, the boundary and interface conditions and the geometry. The articulating surfaces are covered with cartilage layers that are filled with a fluid that plays a major role in load bearing [Mow, V.C., Holmes, M.H., Lai, W.M. (1984) "Survey article: fluid transport and mechanical properties of articular cartilage: a review", Journal of Biomechanics 17(5), 377-394]. Researchers have tended to approximate joint geome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 41 publications
0
32
0
1
Order By: Relevance
“…We also acknowledge that all kinetic measures, including "Intact" measures, were reproduced at 20w post-injury. It is possible that the material properties and geometries of the remaining tissues changed over time in response to mechanical and biological perturbations of the stifle milieu (Frank, et al, 2004;Funakoshi, et al, 2007;Mow, et al, 2005;Ochi, et al, 1997). This could mean that Intact and 4w meniscal force measures may not reflect the earlier time point function exactly.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…We also acknowledge that all kinetic measures, including "Intact" measures, were reproduced at 20w post-injury. It is possible that the material properties and geometries of the remaining tissues changed over time in response to mechanical and biological perturbations of the stifle milieu (Frank, et al, 2004;Funakoshi, et al, 2007;Mow, et al, 2005;Ochi, et al, 1997). This could mean that Intact and 4w meniscal force measures may not reflect the earlier time point function exactly.…”
Section: Discussionmentioning
confidence: 84%
“…Many have hypothesized that loads borne by the remaining structures of the knee are different following ACL tear (Frank, et al, 2004). By and large, in vitro (Allen, et al, 2000;Papageorgiou, et al, 2001) and numerical (Li, et al, 2002) studies have provided significant evidence to support the hypothesis.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…In another study, Ferguson et al 39 used bovine acetabular labrums and again reported the labrum's ability to maintain interstitial fluid and resist the flow of fluid out of the cartilage with compression testing. Adeeb et al 40 noted that the function of the labrum is to reduce the pressure gradient and fluid flow out of the joint tissues thereby decreasing the tensile stresses across the joint's contact areas. Adeeb et al 40 also suggested decreased circumferential stresses at the joint's perimeter are due to the labrum's function of confining the joint.…”
Section: Labral Lesion As a Pathology Requiring Surgery Or Conservatimentioning
confidence: 99%
“…Adeeb et al 40 noted that the function of the labrum is to reduce the pressure gradient and fluid flow out of the joint tissues thereby decreasing the tensile stresses across the joint's contact areas. Adeeb et al 40 also suggested decreased circumferential stresses at the joint's perimeter are due to the labrum's function of confining the joint. Jones 41 noted that both the labrum and joint capsule have important functions of stabilizing the joint by creating a vacuum seal.…”
Section: Labral Lesion As a Pathology Requiring Surgery Or Conservatimentioning
confidence: 99%